CONFLICT RESOLUTION EDUCATION IN MEDINA CONSTITUTION: Contextual Exegesis of Medina Constitution - Mawi Khusni Albar (AL-TAHRIR, 2018)
Abstract: Conflict is an integral part and has a wide variety of types in all aspects of people's lives. This is the responsibility of education because of the potential it possesses to prevent conflicts. Therefore the education of conflict resolution is a suitable idea to resolve conflict issues. The Medina constitution is a monumental work in the history of human life that becomes the spirit of how to create a harmonious life amid diversity. The interpretational method of Medina Constitution is legal hermeneutics which has three meaning areas such as text, context, and contextualization of text meaning to the context. The underlying theory in this research is the theory of conflict resolution education which has three areas to handle conflicts, such as social contradiction changes with structural approaches, improvement of relationship behavior and social interaction, and encouragement of attitude change. The Medina Constitution has fundamental values in social life, namely: togetherness, unity, freedom, religious tolerance, mutual help, justice, equality of rights and obligations, social honor, national defense and peace, piety, amar ma'ruf nahi munkar, and leadership. The contextualization of principles in the Medina charter on conflict resolution education can be discovered relevantly in the following three aspects; structural, behavioral improvement, and attitudinal changes in social relations.الملخص: الصراع هو جزء لا يتجزأ من حياة الإنسان ويتخذ أشكالا مختلفة وهو يحدث في جميع جوانب حياة الناس. هذه هي مسؤولية للتربية ، لأن للتربية القدرة على منع النزاعات ، لذا فإن التثقيف في مجال حل النزاعات هو الفكرة الصحيحة لمعالجة مشكلة الصراع هذه. أما بالنسبة للروح المأخوذة من ميثاق المدينة التي  هي عملاً ضاخما في تاريخ الحياة البشرية حول كيفية خلق حياة متناغمة في تنوع الاجتماعية . إن طريقة تفسير ميثاق المدينة هي التأويل القانوني الذي له ثلاثة جوانب من المعنى ، أي النص ، السياق ، و سياق معنى النص. النظرية الأساس لتطوير هذا البحث هي نظرية تربية حل النزاعات التي لها ثلاثة مجالات للتعامل مع الصراع ، وهي: التغيرات في التناقضات الاجتماعية مع المقاربات الهيكلية ، تحسين سلوك العلاقة والتفاعل الاجتماعي ، وتشجيع التغييرات في المواقف. يمتلك ميثاق المدينة مبادئ في الحياة الاجتماعية ، وهي: التعاون والوحدة والحرية والتسامح الديني ومساعدة الضعفاء والعدالة والمساواة في الحقوق والواجبات والاحترام الاجتماعي والدفاع عن الدولة والسلام والتقوى والامر بالمأروف ونهي عن المنكر  والقيادة. أما فيما يتعلق بوضع المبادئ في ميثاق المدينة في مجال حل النزاعات ، فيمكن إيجازها في ثلاثة جوانب ، هي: المنهج الهيكلي ، السلوكي ، والتغيرات في المواقف في العلاقات الاجتماعية.Abstrak: Konflik merupakan bagian yang tidak terpisahkan dalam kehidupan manusia dan mengambil bentuk yang beraneka rupa dan hampir menyeluruh di segala aspek kehidupan masyarakat. Hal ini merupakan tanggung jawab pendidikan, karena pendidikan memiliki potensi untuk mencegah terjadinya konflik, maka pendidikan resolusi konflik merupakan gagasan yang tepat untuk menyikapi persoalan konflik ini. Adapun ruhnya diambil dari Kosntitusi Madinah yang merupakan karya monumental dalam sejarah kehidupan manusia tentang bagaimana menciptakan kehidupan yang harmonis di tengah keberagaman. Metode penafsiran Konstitusi Madinah adalah legal hermeneutika yang memiliki tiga wilayah pemaknaan, yaitu teks, konteks, dan kontekstualisasi dari makna teks terhadap konteks. Teori yang menjadi dasar pengembangan penelitian ini adalah teori pendidikan resolusi konflik yang mempunyai tiga wilayah penanganan konflik, yaitu perubahan kontradiksi sosial dengan pendekatan struktur, memperbaiki perilaku hubungan dan interaksi sosial, dan mendorong perubahan sikap. Konstitusi Madinah memiliki nilai-nilai mendasar dalam kehidupan sosial, yaitu kebersamaan, persatuan, kebebasan, toleransi beragama, tolong menolong dan membantu yang lemah, keadilan, persamaan hak dan kewajiban, hormoni sosial, bela negara dan perdamaian, kesalehan, amar ma’ruf nahi munkar, dan kepemimpinan. Adapun kontekstualisasi prinsip-prinsip dalam piagam Madinah dalam pendidikan resolusi konflik dapat ditemukan relevansinya dalam tiga aspek, yaitu struktural, perbaikan perilaku, dan perubahan sikap dalam hubungan sosial.